How Politicians Communicate in Social Media: A Cross-Platform Study - Oliveira, Lucas Santos De; Costa, Wesley; Melo, Pedro Olmo Stancioli Vaz De; Benevenuto, Fabrício (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2022)
With the advent of social media, politicians have access to a new way of communicating with their constituents. It made it possible for politicians without television time, considered essential for a campaign, to expose their ideas and reach a large part of the electorate. As it is a relatively recent phenomenon, researchers from different areas of knowledge have found fertile ground to carry out their research. However, most studies focus on analyzing politicians’ communication on only one social media. In this work, we performed a cross-platform analysis of the communication of Brazilian politicians on Facebook, Instagram, and Twitter. We quantified the posts of these politicians, how much they replicate content and the level of engagement on each of the three social networks. In addition, we grouped and characterized the profiles and communication strategies used by these politicians. As a result, we observed that the majority post on the three social networks, there is diversity in the strategic choice of the main media and there are many politicians who only replicate content on the three networks. However, some post a lot of messages and adapt the content for each network, which suggests management by communication professionals on social media. We also verified that there are several communication profiles, from comical to controversial, with the eclectic profile prevailing, which diversifies the style of the posts.